2009
DOI: 10.1194/jlr.m700505-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-rich lipoprotein lipolysis releases neutral and oxidized FFAs that induce endothelial cell inflammation

Abstract: Triglyceride-rich lipoprotein (TGRL) lipolysis products provide a pro-inflammatory stimulus that can alter endothelial barrier function. To probe the mechanism of this lipolysis-induced event, we evaluated the pro-inflammatory potential of lipid classes derived from human postprandial TGRL by lipoprotein lipase (LpL). Incubation of TGRL with LpL for 30 min increased the saturated and unsaturated FFA content of the incubation solutions significantly. Furthermore, concentrations of the hydroxylated linoleates 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(201 citation statements)
references
References 64 publications
6
190
0
5
Order By: Relevance
“…In our study, mRNA levels of pro-inflammatory markers IL-6 and MCP-1 were upregulated by hyperoxia. In this context, it has been demonstrated that lipolysis can produce inflammatory responses in endothelial cells [52]; it is therefore possible that FFA may induce the expression of pro-inflammatory markers in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, mRNA levels of pro-inflammatory markers IL-6 and MCP-1 were upregulated by hyperoxia. In this context, it has been demonstrated that lipolysis can produce inflammatory responses in endothelial cells [52]; it is therefore possible that FFA may induce the expression of pro-inflammatory markers in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicated acute exposure to hydrolyzed TGRLs (TGRL lipolysis products) lead to inflammatory injury in human aortic endothelial cells (22,23,27,28), and we hypothesized similar effects may occur in the vasculature of the brain. In our in vitro model of cultured HBMECs, TEM revealed ultrastructural abnormalities in response to TGRL lipolysis products indicative of lipotoxic injury, including mitochondrial swelling and increased levels of lipid droplets in close proximity to mitochondria at 3 h. To further investigate the particular pathway responsible for this injury, we assayed for production of ROS and detected notably elevated levels of superoxide within 15 min of TGRL lipolysis product treatment that were significantly reduced by concomitant treatment with SOD, suggesting that TGRL lipolysis product-mediated HBMEC injury is dependent, at least in part, on elevated ROS.…”
Section: Discussionmentioning
confidence: 99%
“…This process results in TGRL remnant particle formation and lipolysis products such as phospholipids and fatty acids. Previous studies have shown that TGRL lipolysis products cause aortic endothelial injury, including inflammation, elevated expression of reactive oxygen species (ROS), and increased vascular permeability (22)(23)(24)(25)(26)(27)(28)(29). Additionally, activating transcription factor (ATF) 3 appears to play an important role as a master regulator of inflammation in the aortic endothelium in response to TGRL lipolysis products (22,30).…”
Section: Electron Paramagnetic Resonance Spin Trapping Of Superoxide mentioning
confidence: 99%
“…It has shown that the products of lipolysis such as fatty acids induce inflammation in adipose tissue (23,24). Therefore, we next analyzed the expression of genes that are associated with lipolysis.…”
Section: Uhc1 Has Anti-inflammatory Effects On 3t3-l1 Adipocytes Andmentioning
confidence: 99%